Modelagem matematica e simulação numerica do escoamento liquido-vapor num prato de destilação - Noriler, Dirceu, 1978- (2003)
Orientadores: Maria Regina Wolf Maciel, Henry França Meier, Antonio Andre Chivanga Barros